HCI International 2013 - Posters$1 (BExtended Abstractss International Conference, HCI International 2013, Las Vegas, NV, USA, July 21-26, 2013, Proceedings, Part II - Stephanidis, Constantine; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This is the second of a two-volume set (CCIS 373 and CCIS 374) that constitutes the extended abstracts of the posters presented during the 15th International Conference on Human-Computer Interaction, HCII 2013, held in Las Vegas, USA, in July 2013, jointly with 12 other thematically similar conferences. The total of 1666 papers and 303 posters presented at the HCII 2013 conferences was carefully reviewed and selected from 5210 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The extended abstracts were carefully reviewed and selected for inclusion in this two-volume set. The papers included in this volume are organized in the following topical sections: learning and education; health and medicine; media, art and culture; transport; Web and social media; information search and retrieval; work, collaboration and creativity; text and storytelling; agents, avatars and robots; smart environments; virtual and mixed environments; security and privacy.
Learning and education -- health and medicine -- media, art and culture -- transport -- Web and social media -- information search and retrieval -- work, collaboration and creativity -- text and storytelling -- agents, avatars and robots -- smart environments -- virtual and mixed environments -- security and privacy.
Keywords: Computer science; Medical records -- Data processing; Information storage and retrieval systems; Education; Computer Science; User Interfaces and Human Computer Interaction; Computers and Education; Computer Applications; Health Informatics; Computers and Society; Information Storage and Retrieval